Challenges faced by international postgraduate students at an institution of higher learning: a case study / Ibtesam Abdulla Baroni - Abdulla Baroni, Ibtesam (2011)
This thesis focuses on the challenges faced by international postgraduate students in institutions of high learning. The international students were studying at Universiti Teknologi Mara in Shah Alam. Malaysia. This thesis investigated the reasons why international postgraduate students chose UiTM as an institution of high learning to pursue their studies. In addition, the study investigated the challenges faced by these international postgraduate students and the causes of those challenges as well as their coping strategies. Data was collected through participant observation, and interview sessions. The participants of the study were fifteen international postgraduate students and live Malay students who were their classmates. In addition, two lecturers were purposefully selected for interview sessions. It was found that the two main reasons for international students to choose UiTM, are UiTM being a public university and also because it is an Islamic university. Three challenges faced international students in studying here include academic, social, and emotional challenges. Lack of preparation appeared to be the main cause for those challenges. However, international postgraduate students generally used appropriate coping strategies since the majority of them used focused-problem solving strategies where they attempted to make the necessary changes and faced those challenges. In conclusion, the findings reveal that international students still need a lot of support from this institution in helping them to complete their studies. Further research might look into the benefits which international students obtain in studying abroad. In addition to that, further research on this topic includes in depth details on other variables such as gender, age, nationality, and how stands in contrast to another.